Summary of Research and Outreach Activities during the 2021 Season of the EDEN ISS Antarctic Greenhouse - Vrakking, Vincent; Zabel, Paul; Schubert, Daniel; Dorn, Markus; Bunchek, Jess (2022)
THE EDEN ISS greenhouse is a space-analogue test facility near the German Neumayer Station III (NM-III) in Antarctica. The greenhouse design, construction, and test phase began in 2015, and the facility was shipped to NM-III in January 2018. From 2018 until early 2022, the greenhouse was in continuous operation during every winter-over period, with the 2021 season being the latest to be completed. The purpose of the facility is to enable multidisciplinary research on topics related to plant cultivation on future human space exploration missions. Research on food quality and safety, plant health monitoring, microbiology, system validation, human factors, horticultural sciences, and resource demand was conducted. During the 2021 season, research and operation of the EDEN ISS greenhouse was done as part of a DLR-NASA collaboration with an American on-site operator. Part of this collaboration was testing new crops like chili pepper, broccoli, cauliflower, and beans, which had never been grown inside EDEN ISS. These crops were complemented by a variety of lettuces, mustard greens, herbs, tomatoes, cucumbers, radishes, and kohlrabi. In total, approximately 315 kg of fresh produce was harvested during the 2021 season, which was supplied to the NM-III wintering crew. Frozen and dried plant subsamples were collected and transferred back to Europe and the United States for further investigation. Additional samples were taken from the nutrient delivery subsystem and from surfaces inside the EDEN ISS facility in order to continue the microbiological research activities from previous years. Another research focus was capturing crew time for all activities inside the MTF and select support activities inside NM-III to increase the understanding of work time demand for future food production systems in space. DLR and NASA also continued the numerous outreach activities of the past years. This paper summarizes both the research and the outreach activities during the latest operational season of the EDEN ISS Antarctic greenhouse ...